Modelling of wave and current induced concentration of cohesive sediments - Sorourian, Soroush (University of Ottawa (Canada), 2007)
The current research deals with the numerical modelling of cohesive sediment transport under the action of waves in coastal regions. A new mathematical model for the simulation of mud concentration profiles is proposed and developed. The model aims to improve the prediction of cohesive sediment transport compared to the very few mud transport models currently available, by incorporating several new physical phenomena, such as electrochemical particle cohesion, in the calculation of sediment entrainment, transport and deposition. Cohesive sediments are also important in terms of environmental impacts, particularly due to their association with contaminants that attach to them. Processes that govern the behaviour of cohesive sediments differ significantly from those governing non-cohesive sediments. In addition to the physical complexities of cohesive sediment processes, chemical aspects must be considered as well. In this sense, the electrochemical behaviour of cohesive sediments plays an important role as a stabilizing force against the eroding shear force. All of these factors point to the need for a multi-disciplinary approach in dealing with cohesive sediments. Several theoretical concepts were incorporated in order to better estimate the sediment erosion process and enhance the accuracy of the suspended sediment concentration prediction. Firstly, unlike the case of any previous models, the electrochemical force between cohesive sediment particles has been considered. Secondly, a new approach was used to relate bed resistance to soil characteristics. Thirdly, the prediction of the bed shear stress was refined by relating the wave friction factor to parameters of the model such as bed roughness and median grain diameter. Relating the wave friction factor to grain diameter is incorporated for the first time in cohesive sediment transport models. Fourthly, the time-dependent erosion rate was also considered for the first time in cohesive sediment transport models. The numerically simulated suspended sediment concentration profiles were compared with experimental data. The results of the proposed model agree well with the experimental data, as soon as a steady state condition is achieved. The results of the new numerical models provide a better estimation of the suspended sediment concentration profile compared to the initial model.
Keywords: Engineering, Civil.